(untitled) (International Journal of Studies in Nursing, 2017)
Background: Adverse effects on health in the environments are no trivial matter. Exposure to lead has had devastating consequences for health, especially for children. The purpose of this study was to investigate nursing students’ perception of childhood lead poisoning risk factors. Methods: This was a quantitative, cross-sectional study with a descriptive design. Data were collected from 85 baccalaureate nursing students in a college situated in Northern Indiana, USA. Results: The top five most agreed upon responses, chipping or peeling paint; learning problems; blood testing; inedible objects; and lead removal, had means greater than 4.18, on a 5-point Likert-type scale, which indicates a high level of agreement. Discussion: Some of the survey statements indicated deficits in nursing students’ knowledge of lead poisoning risk factors requiring further teaching and learning. Conclusions: More education related to childhood lead poisoning risk factors may need to be integrated into courses such as nursing fundamentals, pediatrics, and community health.